Zirconocene Catalysis in Organoaluminum Synthesis of 1-Alkenyl Sulfones and Sulfides - Kadikova, Rita N.; Ramazanov, Ilfir R.; Vyatkin, Alexey V.; Dzhemilev, Usein M. (Synthesis, 2017)
The Cp2ZrCl2-catalyzed methylalumination of 1-alkynyl sulfones and 1-alkynyl sulfides with Me3Al, followed by deuterolysis or hydrolysis, affords the corresponding β,β-disubstituted 1-alkenyl sulfones and 1-alkenyl sulfides in high yields. S-Methyl methanethiosulfonate is shown to be a convenient and efficient sulfanylating agent for 1-alkenylaluminum derivatives.
Keywords: alkynyl sulfones; alkynyl sulfides; alkenylaluminums; methylalumination; zirconocene catalysis